2002
DOI: 10.1002/app.11528
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal fusion bonding in semicrystalline thermoplastics

Abstract: ABSTRACT:The development of the interfacial bond strength as a function of bonding conditions has been investigated in two representative semicrystalline thermoplastics, isotactic polypropylene and polyamide 12. If one side of the interface is well above the melting point immediately before contact, more rapid effective bonding is obtained for a given estimated interface temperature than under isothermal conditions. This is discussed in terms of a simple two-parameter model for the critical strain energy relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…The importance of the thermal gradient has also been pointed out in some other investigations 2,12 where, for a given interface temperature above melting temperature, it has been shown that most rapid bonding is obtained for the highest thermal gradients.…”
Section: Interface Strengthmentioning
confidence: 93%
See 2 more Smart Citations
“…The importance of the thermal gradient has also been pointed out in some other investigations 2,12 where, for a given interface temperature above melting temperature, it has been shown that most rapid bonding is obtained for the highest thermal gradients.…”
Section: Interface Strengthmentioning
confidence: 93%
“…The results obtained on each test were the mode of failure and shear strength of the interface, which is calculated by dividing the failure force by the bonding interface area (10 ϫ 13 mm 2 ). Given values of strength are calculated as the average of a minimum of eight specimens.…”
Section: Strength Characterization Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the degree of crystallinity, the healing is reduced. In Plummer et al (2003), the achievement of residual adhesive strength in non-isothermal bonding at interface temperatures below T m is presented.…”
Section: Theoretical Aspects Of Fusion Bondingmentioning
confidence: 99%
“…The manufacturing of semi-crystalline thermoplastic composites in particular requires a well defined thermal process history. (Bureau et al, 2002;Bureau and Denault, 2004;Perrin et al, 2003;Trudel-Boucher et al, 2006;Youssed and Denault, 1998;Plummer et al, 2003;Cho and Kardos, 1995;Ghasemi Nejhad, 1993;Ye et al, 1995;Schultz, 1984). The primary objective of this study is to investigate the influence of the process parameters on the bond strength.…”
Section: Introductionmentioning
confidence: 99%